Tata Kelola Pembangunan Kampung Wisata Lawas Maspati: Analisis Perspektif Kebijakan, Partisipasi Masyarakat, Dan Keberlanjutan. - Cahya Megananda, Astrid Eka Wahyu; Indartuti, Endang (Universitas Gajah Putih, 2023)
A tourism program called Kampung Wisata is being developed by the Surabaya City Government, such as Kampung Lawas Maspati. This village is considered one of the leading cultural assets and tourism potential in the city of Surabaya, with historical value and various cultural attractions. Even though it has profitable potential, its status as a Tourism Village faces a number of challenges, such as the government's weak role in managing cultural assets and modernization trends that threaten its existence. The number of tourists decreased during the Covid-19 pandemic, therefore this research was conducted to present and examine the development process so that tourism continues to operate in the midst of the pandemic. The concept used by researchers is Good Tourism Governance according to Bambang Sunaryo (2013). The data collection technique through observation, interviews and notes, at the Kampung Lawas Maspati Surabaya location is a type of qualitative research. The aim of this research is to apply the principles of Good Tourism Governance in the development of Kampung Lawas Maspati. The findings from researchers indicate that of the 10 principles of Good Tourism Governance, there are 2 principles that have not been fully fulfilled and implemented optimally, namely the principle of environmental tolerance and the principle of program monitoring and evaluation.